Multiple splice isoforms of proteolipid M6B in neurons and oligodendrocytes - Werner, Hauke; Dimou, Leda; Klugmann, Matthias; Nave, Klaus-Armin (Molecular and cellular neuroscience, 2001)
Proteolipids are abundant integral membrane proteins, initially described as structural proteins of CNS myelin. More recently, two neuronal proteins related to proteolipid protein (PLP), termed M6A and M6B, were identified, suggesting a common function of proteolipids in oligodendrocytes and neurons. We have analyzed the X-linked M6B gene and discovered an unexpected complexity of protein isoforms. Two promoters and alternative exons yield at least eight M6B proteins and polypeptides, differentially expressed in neurons and oligodendrocytes. Six isoforms are tetraspan membrane proteins that differ by highly conserved amino- and carboxy-terminal domains, termed α, β, ψ, and ω. In MDCK cells, the β-domain of M6B stabilizes tetraspan proteolipids at the cell surface, whereas non-β isoforms are more abundant in intracellular compartments. Cotransfection experiments suggest a physical interaction of M6B and mutant PLP, when retained in the endoplasmic reticulum, that may also contribute to oligodendrocyte dysfunction in Pelizaeus-Merzbacher disease.